A multi-purpose ultrasonic streaming mixer for integrated magnetic bead ELISAs. (14th September 2015) - Brandhoff, Lukas; Zirath, Helene; Salas, Mariugenia; Haller, Anna; Peham, Johannes; Wiesinger-Mayr, Herbert; Spittler, Andreas; Schnetz, Guntram; Lang, Walter; Vellekoop, Michael J
Abstract: We present an ultrasonic streaming mixer for disposable and on-chip magnetic bead ELISAs. The ultrasonic transducer is placed at system-level to keep cost per chip as low as possible, and is coupled to the chip by means of a solid ultrasonic horn. The system provides mixing of liquids, as well as dispersion of the superparamagnetic beads in the ELISA. Additionally it can be used clean the chamber surface from nonspecifically bound proteins during the washing steps in the ELISA protocol. Using our system the time for the ELISA protocol has been greatly reduced down to 30 min.